UPAYA GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENANAMKAN NILAI-NILAI TAZKIYATUN NAFS PADA SISWA SMPN 1 TEMPULING - Syaiful Dinata (Universitas Mataram, 2022)
The problem of students' bad morals seems to be endless, both actions taken at school and even among the community. Of course this is an important note for the world of education, especially a teacher. This activity aims to find out how the PAI teacher's efforts to instill the values ​​of tazkiyatun nafs in the students of SMPN 1 Tempuling. The results of the activity are expected to be useful as evaluation material so that the application of tazkiyatun nafs values ​​can run better. This research is quantitative with sampling technique that is saturated sample. Data collection techniques are using documentation, interviews, and observations. While the data analysis technique uses descriptive quantitative which is calculated manually obtained through observation and interviews to answer questions from the research. Based on the results of the data analysis carried out, it is known that the efforts made by PAI teachers have succeeded in growing the tazkiyatun nafs values ​​in the students of SMPN 1 Tempuling to be categorized as good. This is illustrated by the observed value, which is 77.94%. The things that become supports that affect the success are role models or examples of attitudes that are practiced by teachers and education staff; good cooperation between teachers, administrative staff, school principals, school guards, and staff in the school canteen. The cultivation of tazkiyatun nafs values ​​is going well which is influenced by the teacher as a role model. The inculcation of tazkiyatun nafs values ​​must be carried out by all elements of the school through activities such as mutual cooperation, weekly recitations, and others.